Pengaruh Talent Management dan Work-Life Balance Terhadap Kinerja Karyawan pada Perumda Air Minum Tirta Bahari Kota Tegal: The Influence of Talent Management and Work-Life Balance on Employee Performance at Perumda Drinking Water Tirta Bahari Tegal City - Ade Dita Ananda Khaerotunnisa; Desy Suryani; Martinus Wahyu Purnomo (PT Cakrawarti Empat Proksi, 2026)
This study is motivated by the phenomenon of high workload and employee complaints regarding Work-Life Balance at Perumda Air Minum Tirta Bahari Tegal City, which is suspected to affect employee performance. The research problems are whether Talent Management and Work-Life Balance affect employee performance, both partially and simultaneously. The objective of this study is to determine the effect of Talent Management and Work-Life Balance on employee performance. This study uses a quantitative survey approach with 100 employees as respondents. Data analysis techniques include validity test, reliability test, classical assumption test, multiple linear regression analysis, t-test, F-test, and coefficient of determination R² using SPSS version 25. The results show that Talent Management has no significant effect on employee performance with a significance value of 0.520 > 0.05. Work-Life Balance has a positive and significant effect on employee performance with a significance value of 0.001 < 0.05. Simultaneously, Talent Management and Work-Life Balance have a significant effect on employee performance with F-count 43.585 > F-table 3.09 and significance 0.001 < 0.05. The Adjusted R Square value of 0.462 indicates that both variables can explain 46.2% of the variation in employee performance, while 53.8% is influenced by other factors outside this study. It is concluded that Work-Life Balance is an important factor in improving employee performance, while Talent Management has not shown a significant effect. The company is advised to maintain and improve policies that support employee Work-Life Balance to optimize performance.